Ceftriaxone associated urolithiasis in a child with hypercalciuria - Lozanovski, Vladimir J.; Gucev, Zoran; Avramoski, V. J.; Kirovski, I.; Makreski, P.; Tasic, V. (Hippokratia, 2011)
We present a 5-year-old boy with pneumonia who complained of right lumbar pain on the 7th day of treatment with Ceftriaxone. Ultrasound examination revealed mild to moderate right hydronephrosis. Under spasmoanalgetic therapy and hydration there was spontaneous passage of three small calculi. Infrared spectroscopy showed that the calculi were composed of calcium-ceftriaxonate. Full metabolic investigation was performed and moderate hypercalciuria was detected, suggesting the role of hypercalciuria in ceftriaxone-associated nephrolithiasis.
Gesehen am 10.11.2022